(3CeGdj GdbGdjs - (3CHh Ydj GdbGdj , ESeGYjd Hf GdbGSe Hf YHOhf Hf gGQhf Hf YjSi Hf eMeO Hf SdeGf, CHh Ydj,J (B356 (3g` s ((3eMeO Hf EHQGgje Hf CMeO Hf SYjO Hf SYO s)
(3ChdgG (B:s
(3CeG HYO(B: (3aEffj deG QCjJ GdYde CfaS HVGYI, hCjbfJ Cf WdHg CaVd JLGQI, aGZJQHJ ddQhGjI hdReJ GdYdeGA ddOQGjI aCeddJ gPG GdcJGH ef MaXj, hChOYJg afhfkG ef GdCNHGQ s
(3BNQgG (B:s
(3EPG eG LdSfG dG JRGd JQhefG Jeje dOj CHjGJfG hghGRf bGd CHhGdMSf(B: (3CfTOfG JRMdg Cj JOaYg, hdG CMSH gPG eMahXfG bGd CHhGdMSf(B: (3CSJJH(B: (3JgjC hGdJCe, hCfLGO(B: (3LeY fLO GfJgi cJGH GdCeGdj s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B13s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3JHUQI GdYfhGf (B:s
(3TQM hGedGA s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs